Kepemimpinan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru di MTs Nurul Huda Pematang Cengal - Neliwati; Mhd Alfi Syahrin; Abdul Halim; Yunisa Indriyani (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to identify and analyze the leadership of Madrasah Heads in Improving the Professional Competence of Teachers at MTs Nurul Huda Pematang Cengal. Data collection for this research was carried out using observation, interviews and documentation methods. Leadership is interpersonal influence, in certain situations and directly through the communication process to achieve one or more specific goals. The head of a madrasah is a teacher who is appointed to occupy a structural position in the madrasah, he is assigned to manage the madrasah. Competency is a collection of knowledge, behavior and skills that teachers must have to achieve learning and educational goals. Professional competence is the ability to master learning material broadly and in depth which enables teachers to guide students to meet the competency standards set out in the National Education Standards. From the results of the analysis, it can be seen that the leadership of the madrasa head in improving the professional competence of teachers at MTs Nurul Huda Pematang Cengal is carried out through several things, including the madrasa head having to provide training or workshops to the teachers, the madrasa head also providing motivation and support to the teachers, head Madrasas also supervise all teachers to continuously improve their quality. Meanwhile, teachers' professional competence is considered good and sufficient, such as having been certified, having attended training, workshops and MGMP.